In Vitro Characterization of a Biaryl Amide Anti-virulence Compound Targeting Candida albicans Filamentation and Biofilm Formation - Romo, Jesus A.; Pierce, Christopher G.; Esqueda, Marisol; Hung, Chiung-Yu; Saville, Stephen. P.; Lopez-Ribot, Jose L. (Frontiers in Cellular and Infection Microbiology, 2018)
We have previously identified a small molecule compound, N-[3-(allyloxy)-phenyl]-4-methoxybenzamide (9029936), that exerts potent inhibitory activity against filamentation and biofilm formation by the Candida albicans SC5314 strain and represents a lead candidate for the development of anti-virulence approaches against C. albicans infections. Here we present data from a series of experiments to further characterize its in vitro activity and drug-like characteristics. We demonstrate the activity of this compound against a panel of C. albicans clinical isolates, including several displaying resistance to current antifungals; as well as against a set of C. albicans gain of function strains in key transcriptional regulators of antifungal drug resistance. The compound also inhibits filamentation and biofilm formation in the closely related species C. dubliniensis, but not C. glabrata or C. tropicalis. Combinatorial studies reveal the potential of compound 9029936 to be used together with currently available conventional antifungals. Results of serial passage experiments indicate that repeated exposure to this compound does not elicit resistance. Viability staining of C. albicans in the presence of high concentrations of compound 9029936 confirms that the compound is not toxic to fungal cells, and cytological staining using image flow cytometry analysis reveals that treatment with the lead compound affects hyphal length, with additional effects on cell wall and integrity of the membrane system. In vitro pharmacological profiling provides further evidence that the lead compound displays a safe profile, underscoring its excellent “drug-like” characteristics. Altogether these results confirm the potential of this compound to be further developed as a true anti-virulence agent for the treatment of C. albicans infections, including those refractory to treatment with conventional antifungal agents.